PENGENALAN AWAL AL-ISLAM, KE’AISYIYAHAN, KEMUHAMMADIYAHAN(AIK) MELALUI GAMBAR DI TK ‘AISYIYAH VII PEKANBARU - Putri Clawson; Minah (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2020)
The purpose of this study is to find out how the initial introduction of learning Al-Islam, Ke'aisyiyahan and Kemuhammadiyahan (AIK) through image media in TK ‘Aisyiyah VII Ex. Labuh Baru Barat Kec. Sekaki Umbrella, Pekanbaru City. This research was conducted at TK Aisyiyah VII Pekanbaru to provide support so that the learning process can run well as expected. This type of research is descriptive qualitative. The study was conducted from February to June. The subjects of the study were the teachers in Aisyiyah VII Kindergarten Pekanbaru. Data collection techniques used in this study were interviews, observation, and documentation. While the data analysis technique is done by analyzing these data and providing interpretation of the data obtained by providing qualitative explanations. The results of this study indicate that the initial introduction of learning Al-Islam, Kemuhammadiyahan and Ke'Aisyiyahan through media images will be more interesting if the teacher has the creativity that is able to attract the attention of children. So that the expected learning is as expected.